Study on Interval-valued Dual Hesitant Fuzzy β Covering Rough Set Model - REN Haowei; WANG Qinghai (Journal of Harbin University of Science and Technology, 2024)
To effectively handle the problem of decision-making with interval-valued hesitant fuzzy information, this paper proposes four models of interval-valued dual hesitant fuzzy β coverage rough sets,which are combined with interval-valued dual hesitant fuzzy set and β covering rough set. Firstly, two types of neighborhood systems are induced from interval-valued dual hesitant fuzzy β coverings, and four different models of interval-valued dual hesitant fuzzy β coverings rough sets are defined. Secondly, the mathematical properties of each model of interval-valued dual hesitant fuzzy β coverings rough sets are studied, and the relationships between the four models of interval-valued dual hesitant fuzzy β coverings rough sets and other relevant models are established. Finally, a multi-attribute decision-making algorithm is designed based on these models, and the applicability of interval-valued dual hesitant fuzzy β coverings rough sets in solving practical problems is effectively validated through practical examples.